Role of contrast-enhanced ultrasound with time-intensity curve analysis about thyroid nodule and parenchyma for differentiating BRAF V600E mutation status - Zhipeng Hu; Rong Xue; Zhixi Liu; Liang Liu; Zheli Gong (PeerJ)
Background The BRAF V600E mutation was proven associated with papillary thyroid cancer (PTC) which has more aggressive behavior and could affect the outcome of PTC. The objective of this study was to observe more contrast-enhanced ultrasound (CEUS) time-intensity curve (TIC)—based quantitative parameters in nodules and surrounding parenchyma and analyze the association between the TIC-based quantitative parameters and BRAF V600E mutation status in patients with PTC. Methods A retrospective analysis of 447 PTC patients was conducted. Prior to thyroidectomy or fine needle aspiration (FNA), all patients had CEUS and had their BRAF V600E mutations examined. Based on their mutation status, the patients were split into two groups. The two groups were compared in terms of sex, age, quantitative CEUS characteristics, pathological findings, vascular invasion, capsular invasion, and cervical lymph node metastases. Results A total of 240 patients were in the mutation negative group and 207 patients were in the BRAF mutation positive group. The BRAF-positive group exhibited significantly higher arrival time (AT) and time to peak enhancement (TTP) of the nodules, among other direct quantitative characteristics. The BRAF-positive mutant nodules showed significantly higher arrival time change and time to peak change compared to the surrounding parenchyma for indirect quantitative metrics. Conclusion The time-dependent quantitative parameters of CEUS time intensity curve in nodules and surrounding parenchyma have clinical value in distinguishing BRAF V600E mutation positive nodules from gene mutation negative nodules. Quantitative CEUS characteristics may be beneficial in detecting the BRAF V600E mutation status and informing the subsequent clinical choice.